Representing magical realism as a strategy for the grotesque narration in Ahmed Saadawi’s Frankenstein in Baghdad - Jumaah, Saif Ali Abbas (Penerbit Universiti Kebangsaan Malaysia, 2024)
Saadawi’s novel Frankenstein in Baghdad vividly portrays the grotesque amidst the backdrop of war-torn Baghdad. The grotesque, in all its different dimensions, is a defining feature of Saadawi's novel. This paper will look at how magical realism works as a narrative strategy for portraying the horrors of conflict in a surreal way. Magical realist strategies and expression of the grotesque, when the line between reality and fantasy is blurred, are viewed and analysed in this study through a close reading of Saadawi's text. This paper investigates the utilisation of magical realism as a narrative strategy to depict the horrors of conflict in a surrealistic manner. Through a meticulous analysis of Saadawi’s text, this study explores how magical realism serves as a conduit for the expression of the grotesque, blurring the lines between reality and fantasy. By delving into the intricate interplay between magical elements and the harsh realities of war, this research aims to unravel the deeper thematic implications embedded within Saadawi’s narrative. By incorporating elements of identity fragmentation, moral uncertainty, and societal disintegration, this investigation seeks to offer a comprehensive understanding of the profound impact of magical realism on the construction of narrative meaning in Frankenstein in Baghdad.